Association between raw milk and human Salmonella dublin infection. - Werner, S B (1979)
Between 1971 and 1975 the mean annual incidence of human Salmonella dublin infection in California increased more than five-fold. Investigation of the increase showed an association with exposure to raw milk in 44 out of 113 cases. Of these 44 patients, 35 had used certified raw milk from a single dairy. Faecal swabs confirmed S dublin infection in the dairy herd and the milk, and so a pasteurisation order was issued. S dublin appears to be an unusually invasive and life-threatening salmonella serotype: 65% of isolations were obtained from non-faecal specimens (mainly blood cultures), 89 patients (80%) were admitted to hospital and 22 patients died. Almost three-quarters of the patients were aged 20 or over, and half had serious underlying diseases, particularly leukaemias and lymphomas. Five patients presented with infected vascular lesions that included aneurysms with abscesses and infections of previous arterial graft sites. The public's increasing desire for a "health food" such as raw milk should be tempered with an appreciation of its attendant risk to health.